2016
DOI: 10.1017/s2078633615000314
|View full text |Cite
|
Sign up to set email alerts
|

Description of production system and on-farm phenotypic characterization of Central Highland and Woyto-Guji goat breeds in Ethiopia

Abstract: SummaryThe study examines phenotypic characterization of Central Highland and Woyto-Guji goat breeds at Meta Robi and Konso districts of Ethiopia. Purposive and random sampling techniques were employed to select sample villages and respondent. For administration of semi-structured questionnaire and phenotypic characterization, a total of 240 households and 601 adult animals, respectively, were selected. The average goat flock size (31.25 ± 22.46) owned per household of Konso was significantly (P< 0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
4
4
1
Order By: Relevance
“…e present study revealed that almost all interviewed respondents housing goats separated from other livestock species and kids also separated from their dams during the night for up to one month. is result is in line with the report of Zergaw et al [23]. In all areas, all of the respondents reported roofed goat shelter in both dry and wet seasons.…”
Section: Management Of Goatssupporting
confidence: 92%
See 1 more Smart Citation
“…e present study revealed that almost all interviewed respondents housing goats separated from other livestock species and kids also separated from their dams during the night for up to one month. is result is in line with the report of Zergaw et al [23]. In all areas, all of the respondents reported roofed goat shelter in both dry and wet seasons.…”
Section: Management Of Goatssupporting
confidence: 92%
“…is result is partly consistent with the report of Gatew et al [21]. Likewise, Zergaw et al [23] noted that natural pasture is the dominant feed source during wet and dry seasons. Nowadays, area closure for soil conservation and expansion of cropland reduces the size of natural pasture.…”
Section: Management Of Goatssupporting
confidence: 92%
“…The current finding contradicts with the report of Alefe (2014) in Shebelle zone of southeastern Ethiopia that none of the respondents practiced fattening and Belete et al (2015) in Bale zone that about 79.2% of the respondents were not practicing fattening. On the other hand, the current finding is lower than that of (Zergaw et al, 2016) who reported 70.4% of respondents practiced goat fattening for Central highland and Woyto-Guji goat type in Konso and Meta Robi districts of Ethiopia. Significant different between districts on types of feed resources may be resulted from different management system of farmers or availability of different feeds in the districts.…”
Section: Fattening Practicescontrasting
confidence: 96%
“…Therefore, the selection of one or more of these traits may increase live body weight of the studied goat populations in respective sex. This current finding is in line with the reports of Hassen et al (2010) and Zergaw et al (2016) that body weight with chest girth have a strong relationship in both sexes. Chest girth, height at withers, and height at pelvic are another selection criterion for this goat populations in meat production in addition to body weight.…”
Section: Correlation Of Quantitative Traitssupporting
confidence: 94%